2014
DOI: 10.1109/tac.2013.2274688
|View full text |Cite
|
Sign up to set email alerts
|

On Stability and LQ Control of MJLS With a Markov Chain With General State Space

Abstract: We study the mean square stability and the LQ control of discrete time Markov Jump Linear Systems where the Markov chain has a general state space. The mean square stability is characterized by the spectral radius of an operator describing the evolution of the second moment of the state vector. Two equivalent tests for the mean square stability are obtained based on the existence of a positive definite solution to a Lyapunov equation and a uniformity result respectively. An algorithm for testing the mean squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…The main result presented in Appendix A.1 states that, under some conditions based on the concepts of (stochastic) stabilizability and detectability, there exists a unique (in the µ-almost everywhere sense) stabilizing positive-semidefinite solution for the control S-coupled algebraic Riccati equations and, as shown in Section 5.2, it provides a solution to the infinite-horizon LQ optimal control problem. Notice that these results, based on the concepts of (stochastic) stabilizability and detectability, are substantially different from the results obtained by Kordonis and Papavassilopoulos (2014).…”
Section: Optimal Controlcontrasting
confidence: 82%
See 2 more Smart Citations
“…The main result presented in Appendix A.1 states that, under some conditions based on the concepts of (stochastic) stabilizability and detectability, there exists a unique (in the µ-almost everywhere sense) stabilizing positive-semidefinite solution for the control S-coupled algebraic Riccati equations and, as shown in Section 5.2, it provides a solution to the infinite-horizon LQ optimal control problem. Notice that these results, based on the concepts of (stochastic) stabilizability and detectability, are substantially different from the results obtained by Kordonis and Papavassilopoulos (2014).…”
Section: Optimal Controlcontrasting
confidence: 82%
“…Only more recently the general state space case, in which the Markov chain takes values in a general state space, started to be analyzed. Regarding some stability results it can be mentioned the papers by Li et al (2012) and Kordonis and Papavassilopoulos (2014), in which the exponential almost sure stability and mean square stability were considered. Assuming that the Markov chain is a positive Harris chain, Li et al (2012) showed in Theorem 4.3 that the uniform exponentially almost sure stability is equivalent to a contractivity condition being satisfied.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, communication delays take a continuum of values and need to be modeled by more general stochastic processes such as Markov processes in [3,15,16]. A notable exception can be found in [23], in which the authors have presented an offline computation method of delay-dependent LQ controllers for systems with continuous-valued Markovian delays. The formulation in [23] requires a solution of a nonlinear vector integral equation called the Riccati integral equation and ignores the intersample behavior of the closed-loop system.…”
mentioning
confidence: 99%
“…By definition, the matrices A and B satisfy A ∈ H n sup and B ∈ H n×m sup . This delaydependent discrete-time system is widely used for the analysis of time-delay systems, e.g., in [9,10,18,23,26,27,34].…”
mentioning
confidence: 99%